1996
DOI: 10.1046/j.1365-2362.1996.1910532.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bile salt hydrophobicity on crystallization of cholesterol in model bile

Abstract: Precipitation of cholesterol crystals is an essential step in gallstone formation. In the present study we found much faster and more extensive precipitation of various cholesterol crystal shapes in whole model biles containing the hydrophobic bile salt taurodeoxycholate than in biles containing the relatively hydrophilic taurocholate. Addition of taurodeoxycholate to isolated cholesterol-phospholipid vesicles also induced more crystallization than taurocholate. Crystallization behaviour in whole model biles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
2
9
1
Order By: Relevance
“…Also, at a variance to the gallbladder biles obtained from untreated gallstone patients, ultra filtered (isotropic) incubated gallbladder biles from ursodeoxycholate treated patients remained totally crystal-free during the study period [46]. Using a well established model bile system in vitro, we also showed that hydrophilic bile salts such as tauroursodeoxycholate completely prevented cholesterol crystallization and protected against more hydrophobic bile salt-induced crystallization [47,69,70] and this is consistent with previous data [71].…”
Section: Pro-crystallization Anti-crystallizationsupporting
confidence: 89%
“…Also, at a variance to the gallbladder biles obtained from untreated gallstone patients, ultra filtered (isotropic) incubated gallbladder biles from ursodeoxycholate treated patients remained totally crystal-free during the study period [46]. Using a well established model bile system in vitro, we also showed that hydrophilic bile salts such as tauroursodeoxycholate completely prevented cholesterol crystallization and protected against more hydrophobic bile salt-induced crystallization [47,69,70] and this is consistent with previous data [71].…”
Section: Pro-crystallization Anti-crystallizationsupporting
confidence: 89%
“…Chemical structure of a cholesterol molecule Numerous investigations of the influence of various chemical environments on crystallization and dissolution pathways of cholesterol molecules have been reported, including those on the effects of solvent type [17][18][19], non-solvent phases [20], temperature [17], pH [21], magnetic field [22], mineral substrates [23,24] and co-existing phases [25][26][27][28], model bile composition [29][30][31], various medicinal plants [32] and synthetic biochemical compounds, such as phospholipids [33], and other sterols [34]. These studies have indicated significant sensitivity of cholesterol crystallization process on many of these physical and chemical factors.…”
Section: Introductionmentioning
confidence: 99%
“…Delay of intestinal transit, associated with gallbladder hypomotility, should be seen in the context of a wide "intestinal disease", since a greater proportion of hepatic bile leads to dihydroxylation, partly mediated by the gut microbiota with a consequent increase of the deoxycholate, strongly hydrophobic and cytotoxic BA. The reuptake in the enterohepatic circle of deoxycholate is able to influence the phenomena of crystallization and nucleation of biliary cholesterol with greater lithogenic effects …”
Section: Discussionmentioning
confidence: 99%